2017
DOI: 10.1080/14767058.2017.1351534
|View full text |Cite
|
Sign up to set email alerts
|

Association of maternal serum homocysteine concentration levels in late stage of pregnancy with preterm births: a nested case–control study

Abstract: Higher maternal serum Hcy levels were associated with preterm birth and neonatal body weight. Elevated maternal serum levels of Hcy might serve as a biomarker for preterm birth prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 12 publications
0
17
0
1
Order By: Relevance
“…Qiu et al (2017) studied maternal serum lipid profiles and homocysteine in late pregnancy and showed higher TC and LDL levels in mothers with preterm delivery than in those with term delivery. In contrast, mothers with term delivery had higher HDL levels compared to those with preterm delivery [29].…”
Section: Discussionmentioning
confidence: 67%
“…Qiu et al (2017) studied maternal serum lipid profiles and homocysteine in late pregnancy and showed higher TC and LDL levels in mothers with preterm delivery than in those with term delivery. In contrast, mothers with term delivery had higher HDL levels compared to those with preterm delivery [29].…”
Section: Discussionmentioning
confidence: 67%
“…These conclusions are supported by the findings of other authors although the evidence is weak. Kramer et al [9] and Qiu et al [10] proved that sPTD was correlated with elevated maternal serum Hcy level during the second and third trimesters, however; Knudtson et al [11] failed to prove such association. Vollset et al [12] in their large Norwegian study showed significantly higher maternal Hcy levels few years following conception in women with history of preterm labor.…”
Section: Discussionmentioning
confidence: 99%
“…According to statistics, perinatal mortality is as high as 70% in low birth weight (LBW) with neonatal weight below 2500 grams (Hack et al 1994;Rutter 1995), most of them are born preterm. Growing evidence has shown that the incidence and development of PTB is a complex process that is influenced by a variety of environmental and genetic factors (He et al 2017;Liu et al 2017;Qiu et al 2017;Xiao et al 2016). Therefore, it is helpful to develop approaches of effective prevention and treatment of neonatal morbidity and mortality by elucidating etiological factors contributing to PTB or LBW.…”
Section: Introductionmentioning
confidence: 99%